Characterization of the microwave-induced boiling behaviour at oil/water interface. (October 2020) - Sonobe, Satoshi; Shibata, Yosuke; Asakuma, Yusuke; Hyde, Anita; Phan, Chi
Highlights: Higher power of pulse microwave is useful for quick response of interfacial tension. Boiling behaviour happens due to higher energy density by the local heating. Our dimensionless number is a good index to characterize the energy density. Abstract: In our recent study, a new dimensionless number for microwave local heating at an interface was proposed for explanation of surfactant desorption behaviour in water and oil system. In this study, interfacial behaviour for both boiling and surfactant desorption at water/decane interface was investigated. In particular, a system of water phase with a non-ionic surfactant (Triton X-100) and NaCl was used. Several pulsed irradiation patterns were employed to vary the microwave energy density, and interfacial tension was measured at each condition. It was found that Triton X-100 layer in NaCl aqueous solution is more resistant to interfacial boiling than the Triton X-405 layer in a previous study. The dimensionless number can be used as an indicator to distinguish stable heating and boiling regions. For industrial practices, preventing boiling is desirable to get surfactant desorption efficiently and stably. The results present a practical method to maximum microwave effect on oil/water interface.